Influence of the whistleblowing system and internal control of fraud prevention (Studies empirical on Committee Sport National Indonesia a Province West Papua) - Priliyanti, Andien Kirana; Andi Candra, Yudas Tadius (Jurnal Mantik, 2024)
The objective of this research is to ascertain how the Indonesian National Sports Committee (KONI) West Papua Province prevents fraud by means of internal control and the whistleblower system. The numerous instances of grant fund corruption in Indonesian sports organizations served as the impetus for this study. All employees of KONI West Papua received questionnaires as part of the quantitative research strategy. The findings of the research show that the whistleblower system and internal controls have a large and positive impact on fraud prevention. Furthermore, these factors together have a major impact on fraud prevention. These results show that building a strong internal control framework and implementing an efficient whistleblower mechanism can be a proactive step in stopping fraud in companies, especially in athletic organizations like KONI. It is essential to conduct training for all members of the organization on the importance of internal controls and how to report violations. Additionally, clear policies and support from top management are necessary to create a culture of transparency and accountability. This study provides a significant addition to Indonesia's efforts to create a more comprehensive fraud prevention system